2001
DOI: 10.1128/aac.45.12.3482-3486.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Once-Weekly Rifapentine and Moxifloxacin Regimens against Mycobacterium tuberculosis in Mice

Abstract: Mice infected with 1.6 x 10(7) CFU of Mycobacterium tuberculosis were treated 14 days later for 6 months with a regimen of once-weekly 10 mg of rifapentine and 75 mg of isoniazid per kg of body weight supplemented with either 150 mg of streptomycin per kg or 100 mg of moxifloxacin per kg during either both the 2-week daily initial and once-weekly continuation phases or only in the daily 2-week initial phase. On completion of treatment, all lung cultures were negative, except for three mice, each with a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 15 publications
2
60
0
1
Order By: Relevance
“…Furthermore, in an early bactericidal activity study of the rifamycins it has been suggested that the most effective dose of RPT may lie between 15 and 20 mg/kg (13). Additional improvement of RPTbased regimens might come from incorporating moxifloxacin (MXF), a new fluoroquinolone with potent bactericidal against Mycobacterium tuberculosis and a half-life close to that of RPT (14)(15)(16). It has been demonstrated in the murine model that inclusion of MXF during the initial and continuation phases of a largely once-weekly INH-RPT 10 mg/kg regimen significantly improves sterilizing activity and prevents the selection of rifamycin monoresistance (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in an early bactericidal activity study of the rifamycins it has been suggested that the most effective dose of RPT may lie between 15 and 20 mg/kg (13). Additional improvement of RPTbased regimens might come from incorporating moxifloxacin (MXF), a new fluoroquinolone with potent bactericidal against Mycobacterium tuberculosis and a half-life close to that of RPT (14)(15)(16). It has been demonstrated in the murine model that inclusion of MXF during the initial and continuation phases of a largely once-weekly INH-RPT 10 mg/kg regimen significantly improves sterilizing activity and prevents the selection of rifamycin monoresistance (14).…”
mentioning
confidence: 99%
“…Additional improvement of RPTbased regimens might come from incorporating moxifloxacin (MXF), a new fluoroquinolone with potent bactericidal against Mycobacterium tuberculosis and a half-life close to that of RPT (14)(15)(16). It has been demonstrated in the murine model that inclusion of MXF during the initial and continuation phases of a largely once-weekly INH-RPT 10 mg/kg regimen significantly improves sterilizing activity and prevents the selection of rifamycin monoresistance (14). However, it is unknown whether the addition of MXF to INH-RPT or substitution of MXF for INH would confer the greatest increase in sterilizing activity.…”
mentioning
confidence: 99%
“…Moxifloxacin im Tierversuch auch eine sterilisierende, d.h. eine auf sich nicht replizierende Bakterien wirkende Komponente (Lounis, Bentoucha et al 2001). …”
Section: Die Bedeutung Von Chinolonen Und Ihrer Resistenztestungunclassified
“…Moxifloxacin is a fluoroquinolone that has potent in-vitro activity against MDR-TB (Ji et al, 1998;Gillespie and Billington, 1999). Earlier studies of moxifloxacin in murine models of tuberculosis showed that it had good bactericidal activity that was additive to isoniazi (Miyazaki et al, 1999;Lounis et al, 2001). Though there are several clinic studies (Burman et al, 2006;Conde et al, 2009;Dorman et al, 2009) about moxifloxacin in treatment of MDR-TB, the conclusions of which are not credible because of small sample size and lacks of systemic evaluation of methodologic quality.…”
Section: Introductionmentioning
confidence: 99%